Prevalence, outcome and conduct of in-hospital cardiopulmonary resuscitation in government hospitals of Nepal - Pawan Kumar Hamal; Surendra Kunwar; Kapil Gautam; Ramesh Bhattarai; Rupesh Kumar Yadav; Ritesh Lamsal; Radeep Singh; Sonam Pathak; Nabin Pokhrel (PLoS ONE, 2025)
Introduction Cardiopulmonary resuscitation (CPR) is an evidence-based intervention that saves lives. In low- and middle-income countries like Nepal, the occurrence of the problem and its outcome are seldom studied. The study aims to highlight the prevalence, performance, and outcome of CPR in government hospitals of Nepal. Methods A mixed method study was done for two months in central and provincial government hospitals of Nepal. A total of 80 resuscitations were evaluated using a questionnaire based on the American Heart Association 2020 guidelines for cardiopulmonary resuscitation. An in-depth interview was conducted with 15 active participants of the resuscitation in different sites. Thematic analysis was done using the framework of the chain of survival of arrest victims. Results The overall prevalence of CPR was found to be 1.92% [95% CI: 0.01,0.02] with 5.4% in central hospitals and 0.65% in provincial hospitals with 60% cardiac arrests occurring in the intensive care unit. Estimated time from recognition of the arrest to initiating CPR was 1.9 ±1.4 minutes. Asystole 66.25% was the commonest arrest rhythm and 21.25% had difficulty interpreting rhythm. Only 11.25% of the victims had return of spontaneous circulation and were subsequently transferred for post-arrest care. The qualitative analysis highlighted the lack of trained staff, a dedicated system, feedback mechanism, and provision of post-arrest care. Conclusion Across various level of Nepal’s healthcare system, cardiopulmonary resuscitation is prevalent with poor performance and outcome. To improve outcomes, it is essential to implement standardized procedures and ensure high quality resuscitation delivery before and after the event supported by well-trained healthcare personnel and adequate infrastructure.